60‐4: Mechanically Robust High‐Performance Flexible Oxide TFTs with Imbedded Buried CNT Electrode for Bendable Displays. Issue 1 (30th May 2018) - Billah, Mohammad Masum; Park, Min Sang; Saha, Jewel Kumer; Hasan, Md Mehedi; Han, Ji-Ung; Hwang, Mangyu; Jang, Jin
Abstract : We demonstrate highly robust flexible a‐IGZO thin‐film transistors (TFTs) with imbedded carbon nano‐tube (CNT) buried electrode (BE) in between polyimide (PI) substrate. The excellent mechanical durability of flexible TFTs on thin wrinkle‐free and the self‐standing PI substrate with imbedded CNT BE has been demonstrated. The strain on the TFT can be reduced by the imbedded CNT electrode which is calculated from the 3D‐TCAD simulation.